Magnesium sulphate therapy in eclampsia and pre-eclampsia - Sagar, Smriti; Natu, Neeta; Chandwaskar, Nootan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal and perinatal mortality and morbidity remains high during pregnancy in the presence of eclampsia, it can have severe adverse effects on mother and the fetus. So, its management should be a top priority. The objective of the present research was to study the effect of magnesium sulphate in control of imminent eclampsia and eclampsia. Methods: 19 cases of eclampsia and 185 cases of imminent eclampsia were treated with standardized magnesium sulphate. The outcome measures in terms of recurrence of convulsions, maternal and neonatal outcome, etc. were seen. Results: Most common age group in both the groups were 21-30 years (i.e. 78.9% with eclampsia and 75.7% with imminent eclampsia). In both the groups, majority of the women were primigravidae. In eclampsia group, 9 (47.4%) women had 1 episode of convulsion, 8 (42.1%) women had two episodes of convulsions, 1 (5.3%) women each had 3 and 4 episodes of convulsions, while there were no convulsions in imminent eclampsia women (‘t’ value = 28.558, df=202, p=0.000). Vomiting and headache (94.7%) were the most common premonitory symptoms in eclampsia group, followed by edema in 68.4% women, while in imminent eclampsia 64.9% women had headache, 57.8% women had edema and 43.2% had vomiting. Recurrence of convulsions were seen in 4 (21.1%) women of the eclampsia group even after giving maintenance dose and additional dose of magnesium sulphate. 1 (5.3%) death was seen in eclampsia group and none in the imminent eclampsia group. Neonatal mortality in eclampsia group (47.4%) was higher than imminent eclampsia group (11.7%), which was statistically significant (Z value = 3.05, p=0.002). Conclusions: Magnesium sulphate regimen was effective in control of convulsions in eclampsia and as prophylaxis in imminent eclampsia.